2013
DOI: 10.3892/etm.2013.1259
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SENP1 induces radiosensitization in lung cancer cells

Abstract: Lung cancer is one of the most common and lethal types of malignancy. To date, radiotherapy and chemotherapy have been used as the two major treatment methods. However, radioresistance of lung cancer remains a therapeutic hindrance. The aim of this study was to identify whether small ubiquitin-related modifier (SUMO)-specific protease 1 (SENP1) is a marker of radioresistance that may serve as a target for enhancing the efficacy of lung carcinoma radiotherapy. SENP1 was observed to be overexpressed in lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…SENP1 acts also as a factor to develop tolerance to hypoxia, contributing to hypoxia-driven vascular endothelial growth factor expression and angiogenesis in endothelial cells, 154,155 and protects against hydrogen peroxide-induced cell death, whereas its depletion enhances apoptosis in vitro. 156,157 It is, therefore, obvious that the simple model of a beneficial role of enhanced SUMOylation Figure 2. Effect of differential SUMOylation of dynaminrelated protein (Drp1) on apoptotic cell death in various cell types.…”
Section: Cardiac Stress Adaptationmentioning
confidence: 99%
“…SENP1 acts also as a factor to develop tolerance to hypoxia, contributing to hypoxia-driven vascular endothelial growth factor expression and angiogenesis in endothelial cells, 154,155 and protects against hydrogen peroxide-induced cell death, whereas its depletion enhances apoptosis in vitro. 156,157 It is, therefore, obvious that the simple model of a beneficial role of enhanced SUMOylation Figure 2. Effect of differential SUMOylation of dynaminrelated protein (Drp1) on apoptotic cell death in various cell types.…”
Section: Cardiac Stress Adaptationmentioning
confidence: 99%
“…However, knockdown of SENP1 had no effect on the SUMOylation of PML-RARα in NB4 cells, even after NB4 cells were treated with 1 µΜ As 2 O 3 (data not shown), suggesting the possibility that other members of the SENP family may be involved in regulating the level of SUMOylated PML-RARα, which remains to be further investigated. It has been reported that knockdown of SENP1 could promote drug-induced cell apoptosis in MEF and HEK 293T cells, as well as lung cancer and Burkitt lymphoma cells (1719). However, our results revealed that downregulation of SENP1 had no effect on the spontaneous apoptosis or differentiation of NB4 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that SENP1 is overexpressed and contributes significantly to the development and progression of tumors, including prostatic intraepithelial neoplasia, colon cancer and pancreatic cancer (1416). Previous studies have revealed that deficiency or downregulation of SENP1 could induce radiosensitization in lung cancer cells (17), promote endoplasmic reticulum (ER) stress-induced apoptosis in MEF and HEK 293T cells (18), and increase apoptosis in Burkitt lymphoma cells (19). Furthermore, SENP1 is also involved in the formation of PML protein nuclear bodies (20,21), which were originally characterized as part of a fusion protein with PML-RARα in patients with APL (22).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of SENP1 contributes to the abnormity of the cell nucleus and mitochondria . It has been reported that the expression of SENP1 was upregulated in NSCLC …”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a target of HIF‐1α, and the activation of HIF‐1α/VEGF signaling pathway is essential for angiogenesis, tumor angiogenesis, atherosclerosis, and diabetes mellitus . In contrast, the suppression of SENP1, HIF‐1α, and VEGF was reported to suppress tumor development and aggressiveness of cancers, including NSCLC . However, there was less information on the in vivo association of SENP1 expression with chemotherapy resistance of NSCLC.…”
Section: Introductionmentioning
confidence: 99%